Integrating therapies for surgical adult soft tissue sarcoma patients - Milgrom, Daniel P.; Sehdev, Amikar; Kays, Joshua K.; Koniaris, Leonidas G. (Translational Gastroenterology and Hepatology; Vol 3 (November 2018): Translational Gastroenterology and Hepatology, 2018)
Sarcomas are an uncommon group of over 50 different individual histological malignancies arising from mesenchymal (non-epithelial or connective) tissues. Overall, they constitute 1% of human malignancies with an annual incidence rate of fewer than 5 patients per million. Sarcoma may arise from any mesenchymal cell lineages including fat, muscle, or other connective tissues. Due to the rarity of these groups of malignancies, many subtypes were, and still today, are managed as a single entity. This review focused on soft tissue sarcomas with an emphasis on how to integrate therapies for patients with this rare disorder. The role for surgical resection in cure and palliation as well as the relative benefits of adjuvant therapies such as chemotherapy and radiation therapy are discussed.